Efficient Synthesis of tert‐Butyl 2, 4‐Dialkynylated and 2‐Alkynylated‐4‐Arylated‐1H‐Imidazole‐1‐Carboxylate via Regioselective Sonogashira Cross‐Coupling Reaction. Issue 31 (19th August 2021) - Jismy, Badr; El Qami, Abdelkarim; Jacquemin, Johan; Guillot, Regis; Tikad, Abdellatif; Abarbri, Mohamed
Abstract: An efficient regioselective cross‐coupling reactions of tert ‐butyl 2, 4‐dibrominated‐5‐methyl‐1 H ‐imidazole‐1‐carboxylate is reported. This new synthetic route runs under simple and mild conditions and selectively gives an easy access to 2, 4‐dialkynylated and 2‐alkynylated‐4‐arylated‐1 H ‐imidazole‐1‐carboxylate in good to excellent yields. Abstract : An efficient and suitable selective Sonogashira cross‐coupling reaction to access unknown 2, 4‐dialkynylated and 2‐alkynylated‐4‐arylated‐5‐methyl‐1 H ‐imidazole‐1‐carboxylates has been developed.